Cardiovascular diseases in patients with cancer: A comprehensive review of epidemiological trends, cardiac complications, and prognostic implications - Alshahrani Ali A; Kontopantelis Evangelos; Morgan Catharine; Ravindrarajah Rathi; Martin Glen P; Mamas Mamas A (中华医学杂志英文版, 2025)
This article provides an overview of the current evidence on the epidemiology, overlapping risk factors, and pathophysiology of cardiovascular disease (CVD) in patients with cancer. It explores the cardiotoxic effects of anticancer therapy and their impact on prognosis. Although cancer survival rates have improved over the last two decades, the risk of CVD has risen over time in patients with cancer. CVD and cancer share similar risk factors and a common pathophysiology involving inflammation. Many chemotherapeutic agents used to treat cancer are associated with cardiovascular complications (such as heart failure, myocardial infarction, and thrombosis). Current evidence indicates a significant burden of CVD in patients with cancer, particularly in the first year following cancer diagnosis, with elevated risk persisting beyond this period. This short- and long-term risk of CVD may vary depending on the cancer type and treatment regimen. Early identification of potential cardiovascular risk in patients with can